Evaluasi fisikokimia dan tingkat kesukaan chips mocaf dan kacang merah sebagai makanan selingan untuk penderita anemia - Meifitri Heryanti; Putu Riska Prayoga; Silvia Anggun Yustita; Hudiya Arini Haq; Yosfi Rahmi; Ida Restyani; Lola Ayu Istifiani (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The prevalence of anemia among adolescent females in Indonesia grew from 22.7% in 2013 to 32% in 2018. Anemia is frequently caused by an iron deficiency. Efforts that can be made include eating iron-rich foods like mocaf and red bean.Objectives: The purpose of this research is to evaluate the physicochemical properties and level of preference for chips made from mocaf flour and red bean flour as a snack for anemia. Methods: This study used a real experimental design with a completely random design. This research was carried out from August 2023 to December 2023. There were 4 treatment groups with 3 repetitions with the ratio (mocaf flour: red bean flour), namely P0 (100%:0%), P1 (40%:60%), P2 (50%:50%), and P3 (60%:40%). Physicochemical property testing was carried out at the Food Safety and Quality Testing Laboratory, and the level of preference test was carried out at the Dietetics and Culinary Laboratory, Brawijaya University. Statistical analysis used the parametric One-Way ANOVA or One Way ANOVA Welch test with post hoc Bonferroni or Games-Howell and non-parametric Kruskal-Wallis test with post hoc Mann WhitneyResults: There were significant differences (p<0.05) in physicochemical evaluation such as protein, energy, water content, ash content, iron content, hardness, breaking strength, and level of preference parameters such as color, taste, aroma, and overall appearance. Apart from that, there were no statistical differences in fat, carbohydrate, or texture levels (p>0.05).Conclusion: The addition of mocaf flour and red bean flour has a significant effect on the physicochemical evaluation, especially on parameters such as protein, energy, water content, ash content, iron content, hardness, breaking strength and the level of preference for color, taste, aroma and overall appearance.